2015
DOI: 10.1016/s1474-4422(14)70231-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of progressive multiple sclerosis: what works, what does not, and what is needed

Abstract: Disease-modifying drugs have mostly failed as treatments for progressive multiple sclerosis. Management of the disease therefore solely aims to minimise symptoms and, if possible, improve function. The degree to which this approach is based on empirical data derived from studies of progressive disease or whether treatment decisions are based on what is known about relapsing-remitting disease remains unclear. Symptoms rated as important by patients with multiple sclerosis include balance and mobility impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
179
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(183 citation statements)
references
References 121 publications
2
179
0
2
Order By: Relevance
“…Besides, it might currently be the only treatment option leading to symptomatic improvement for patients with progressive MS types. 47 Furthermore, exercise therapy is safe: a recent review identified a slightly reduced relapse rate in the exercise training group compared with non-exercising controls and only few adverse events (1.2% and 2.0% in control and training groups, respectively). 36 Nowadays, first translational evidence 48 is being generated with observed clinical improvements after training on a balance board in 27 patients with MS being associated with identified neural changes in the microstructure of superior cerebellar peduncles.…”
Section: Non-medical Treatment Options: Active Rehabilitation Treatmentmentioning
confidence: 99%
“…Besides, it might currently be the only treatment option leading to symptomatic improvement for patients with progressive MS types. 47 Furthermore, exercise therapy is safe: a recent review identified a slightly reduced relapse rate in the exercise training group compared with non-exercising controls and only few adverse events (1.2% and 2.0% in control and training groups, respectively). 36 Nowadays, first translational evidence 48 is being generated with observed clinical improvements after training on a balance board in 27 patients with MS being associated with identified neural changes in the microstructure of superior cerebellar peduncles.…”
Section: Non-medical Treatment Options: Active Rehabilitation Treatmentmentioning
confidence: 99%
“…The outlook for patients with more progressive disease, however, is less optimistic. 92 Nevertheless, at most stages of MS there remains a great need for personalised regimens that aim to maximise resilience and Providing such intensive individual attention to all patients with MS is a challenge since access to treatments and services in MS across Europe is highly variable and often limited by the availability of healthcare resources. 93 Neurorehabilitation takes many forms depending on the various physical or mental manifestations of the disease in each patient and the problems they encounter.…”
Section: Resultsmentioning
confidence: 99%
“…According to this hypothesis, progression in MS would be present from the beginning of illness and progressive cytodegeneration would underlie all disease processes. Resolution of these conflicting ideas is unresolved, nonetheless both suggest that treatment of PMS, preferable at the early stages of disease, should be based on a combination of antiinflammatory, regenerative and neuroprotective strategies [11,17,18]. Nevertheless, although inflammatory and neurodegenerative events act in concert to induce MSspecific brain damage their relevance changes during the course of chronic disease evolution.…”
Section: Introductionmentioning
confidence: 99%